Prognostic value of mesorectal package area in patients with locally advanced rectal cancer following neoadjuvant chemoradiotherapy: A retrospective cohort study - Guan, Bingjie; Huang, Xinmin; Xia, Huang; Guan, Guoxian; Xu, Benhua (Frontiers in Oncology, 2022)
Background The aim of this study was to explore the most effective Inflammation, magnetic resonance imaging (MRI), and nutrition markers for survival and pathology complete response(pCR) in locally advanced rectal cancer(LARC) patients. Methods A total of 278 LARC patients undergoing neoadjuvant chemoradiotherapy (NCRT) and radical surgery from 2016 to 2019 were included. The X-tile method was used to selected the optimal cut-off points for the mesorectal package area(MPA), advanced lung cancer inflammation index(ALI), prognostic nutritional index(PNI), systemic immune-inflammation index(SII); and neutrophil-to-lymphocyte(NLR), platelet-to-lymphocyte(PLR), and monocyte-to-lymphocyte(MLR) score. COX regression analysis were used to identify risk factors of disease-free survival(DFS). To discover pCR risk factors, logistic regression analysis were employed. A predictive nomogram for DFS was constructed. Results According to the LASSO analysis, the MPA was the only significant predictor for the DFS in LARC patients. K-M analysis demonstrated that groups with higher MPA, PNI, SII, NLR, MLR, and ALI score had improved DFS(all P<0.05). ROC analsis revealed the MPA and PNI could accurately predict the pCR in LARC patients after NCRT. The MPA score and NLR score were found to be independent predictors of DFS after NCRT using Cox regression analysis. Logistical regression analysis demonstrated the MPA score, PNI score, and pre-NCRT cN stage were all independent predictors of pCR in LARC patients following NCRT. Recursive partitioning analysis (RPA) and time-independent receiver operating characteristic ROC curve analysis demonstrated that MAP score was the most important predictor of pCR and prognosis in LARC patients following NCRT. Conclusions MPA was identified as the most effective marker for MRI, and the prognostic value was further confirmed by Time-ROC analysis. More intense adjuvant treatment could be considered for lower MPA score patients with LARC following NCRT.Obesity in the pelvis is hopeful in comprehending the prognosis prediction of LARC patients after NCRT.